2020
DOI: 10.1186/s12885-020-07286-2
|View full text |Cite
|
Sign up to set email alerts
|

An integrative pan-cancer investigation reveals common genetic and transcriptional alterations of AMPK pathway genes as important predictors of clinical outcomes across major cancer types

Abstract: Background: The AMP-activated protein kinase (AMPK) is an evolutionarily conserved regulator of cellular energy homeostasis. As a nexus for transducing metabolic signals, AMPK cooperates with other energy-sensing pathways to modulate cellular responses to metabolic stressors. With metabolic reprogramming being a hallmark of cancer, the utility of agents targeting AMPK has received continued scrutiny and results have demonstrated conflicting effects of AMPK activation in tumorigenesis. Harnessing multi-omics da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The activation of STK11 could also be involved in the activation of phosphofructokinase 1 (PFK1) and PFK2, which are part of the glycolysis process [ 37 ]. These proteins and the AMPK pathway are of particular interest because of their involvement in cancer multidrug resistance and their use for the prediction of clinical outcome of major cancer types [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The activation of STK11 could also be involved in the activation of phosphofructokinase 1 (PFK1) and PFK2, which are part of the glycolysis process [ 37 ]. These proteins and the AMPK pathway are of particular interest because of their involvement in cancer multidrug resistance and their use for the prediction of clinical outcome of major cancer types [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous pre-clinical evidences stating the dual nature of AMPK in cancer. However, the controversy over the positive and negative regulatory effects of AMPK in the context of cancer cannot Frontiers in Immunology frontiersin.org be resolved without substantial clinical evidence (126). The research pertaining to the clinical outcomes of differential regulation of AMPK signaling in cancer is still in a nascent stage.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…The aforementioned data indicates that the pro- or anti-tumorigenic roles of AMPK are likely to be dependent on the levels of the nutrients in the TME ( 125 ). Notably, another independent study involving a pan-cancer analysis using multi-omics approach reveals that genetic as well as transcriptional aberrations in AMPK signaling elicits tissue-dependent pro- or anti-tumor impacts across major cancer types ( 126 ).…”
Section: The Pro-tumorigenic Functions Of Ampk: Double-edged Sword In...mentioning
confidence: 99%
“…However, some studies demonstrated that the abnormal expression and activation of AMPK in cancer cells plays an important role in promoting proliferation, metastasis, and maintaining cancer cell survival under stress conditions [ 23 , 24 , 25 ]. A study investigating 92 pathway genes of AMPK in 21 types of cancers indicated opposite effects of AMPK on cancer progression [ 26 ]. Therefore, biomolecules in cancer cells and pharmacological modulators, including metformin, tamoxifen, as well as some other natural products, can manage cancer progression by regulating activities of AMPK and its downstream targets.…”
Section: Introductionmentioning
confidence: 99%